Intellectual Virtue : Perspectives from Ethics and Epistemology. - DePaul, Michael R. (Michael Raymond), 1954- (Oxford University Press, UK, 2007)
The idea of a virtue has traditionally been important in ethics, but only recently has gained attention as an idea that can explain how we ought to form beliefs as well as how we ought to act. Moral philosophers and epistemologists have different approaches to the idea of intellectual virtue; here, Michael DePaul and Linda Zagzebski bring work from both fields together for the first time to address all of the important issues. It will be required reading for anyone working in either. field. - ;Virtue ethics has attracted a lot of attention over the past few decades, and more recently there has.